Brief Report: Dapivirine Vaginal Ring Use Does Not Diminish the Effectiveness of Hormonal Contraception. (1st October 2017) - Balkus, Jennifer E.; Palanee-Phillips, Thesla; Reddy, Krishnaveni; Siva, Samantha; Harkoo, Ishana; Nakabiito, Clemensia; Kintu, Kenneth; Nair, Gonasangrie; Chappell, Catherine; Kiweewa, Flavia Matovu; Kabwigu, Samuel; Naidoo, Logashvari; et al.
Abstract : Objective: To evaluate the potential for a clinically relevant drug–drug interaction with concomitant use of a dapivirine vaginal ring, a novel antiretroviral-based HIV-1 prevention strategy, and hormonal contraception by examining contraceptive efficacies with and without dapivirine ring use. Design: A secondary analysis of women participating in MTN-020/ASPIRE, a randomized, double-blind, placebo-controlled trial of the dapivirine vaginal ring for HIV-1 prevention. Methods: Use of a highly effective method of contraception was an eligibility criterion for study participation. Urine pregnancy tests were performed monthly. Pregnancy incidence by arm was calculated separately for each hormonal contraceptive method and compared using an Andersen–Gill proportional hazards model stratified by site and censored at HIV-1 infection. Results: Of 2629 women enrolled, 2310 women returned for follow-up and reported using a hormonal contraceptive method at any point during study participation (1139 in the dapivirine arm and 1171 in the placebo arm). Pregnancy incidence in the dapivirine arm versus placebo among women using injectable depot medroxyprogesterone acetate was 0.43% vs. 0.54%, among women using injectable norethisterone enanthate was 1.15% vs. 0%, among women using hormonal implants was 0.22% vs. 0.69%, and among women using oral contraceptive pills was 32.26% vs. 28.01%. Pregnancy incidence did not differ by study arm for any of the hormonal contraceptive methods. Conclusions: Use of the dapivirine ring does not reduce the effectiveness of hormonal contraceptives for pregnancy prevention. Oral contraceptive pill use was associated with high pregnancy incidence, potentially because of poor pill adherence. Injectable and implantable methods were highly effective in preventing pregnancy.